Peran Kepemimpinan Untuk Meningkatkan Profesionalisme Guru Pesantren Terpadu Raudhatul Jannah Kota Subulussalam - Miranti Adelia Afda; Amiruddin Siahaan; Inom Nasution (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
The primary responsibility of a leadership role in education is to create an environment conducive to effective teaching and learning, ensuring that teachers are able to deliver instruction accurately and students can learn effectively. This research examines the role of Islamic boarding school leaders to increase teacher professionalism, the leadership role carried out at the Raudhatul Jannah Integrated Islamic Boarding School to increase teacher professionalism. Furthermore, researchers observe that there are still various obstacles that hinder the achievement of teacher professionalism at the Radhatul Jannah Integrated Islamic Boarding School, Subulussalam City. This research uses a methodology. qualitative research. The aim of this research approach is to provide a detailed description of the existence of teaching staff or teachers at the Raudhatul Jannah Integrated Islamic Boarding School located in Subulussalam City. The results of this research explain that, the role of leaders to increase the professionalism of Raudhatul Jannah Integrated Islamic Boarding School teachers in Subulussalam City is leaders who act as Educators, Managers, Leaders of Raudhatul Jannah Integrated Islamic Boarding Schools also act as Administrators, Leaders of Raudhatul Jannah Integrated Islamic Boarding Schools also act as Supervisors, Leaders of Integrated Islamic Boarding Schools Raudhatul Jannah also acts as a Leader Innovator and Leader of the Integrated Islamic Boarding School. Raudhatul Jannah also acts as a Motivator.